Analisis Pemanfaatan Aplikasi Tiktok Sebagai Media Pembelajaran Teks Drama - Widya Utami (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Drama is a work of art composed of dialogue containing stories or events involving conflict between characters. Learning drama texts is acting or staging drama. Utilizing the Tik Tok application as a learning medium to demonstrate drama texts is one way to increase teacher creativity in utilizing the latest learning media in accordance with current developments as well as increasing students' creativity and interest in learning in following the ongoing learning process. This research is a qualitative descriptive study with the subject of class VIII students at SMP PAB 8 Sampali. The research results show that 1) the Tik Tok application can be a learning medium to support the learning process, 2) the Tik Tok application as a learning medium demonstrating drama texts gets a positive response from students. The conclusion of this research is that the Tik Tok application is an application that can be used as a learning medium in the learning process and this application also received a positive response from students regarding its use as a learning medium for demonstrating drama texts.